Sistem pembayaran saman secara MOBILE berorientasikan CRM bagi Polis Diraja Malaysia - Osman, Heti Aznin (2006)
Online summons payment for the Polis Diraja Malaysia (PDRM) is a way to initiate the values of CRM in order to achieve their motto. This system is believed to be able to assist the PDRM for the mobile summons payment and also provide easiness for the community to pay up their summons. PDAs are the first devices to be used in the system. The system is being developed by using the prototype methodology. On the programming section, the system used was Microsoft Visual Basic.Net as it is most suitable to be used to develop the system. This system can be used for processes such as summons checking and summons payment. All this processes uses the mobile system and is being sent to the server through the Internet. All information sent will reach the designated database. The system is simple and easy to use as the user interface created is also user-friendly.